Pengaruh Pengembangan Kompetensi terhadap Produktivitas Kerja Pegawai di Lingkungan Kedeputian Bidang Pengawasan dan Pengendalian Badan Kepegawaian Negara (BKN) Pusat - Angga Alfianto; Moh Taufan Nugroho (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Employee competency development is a key aspect in increasing performance productivity within the State Civil Service Agency (BKN). This research aims to identify the influence of competency development on employee performance productivity at BKN. The research method used is a survey and data analysis using linear regression techniques. This research was carried out in 2024, with the research locus at the Deputy for Supervision and Control of BKN. The research sample consisted of employees involved in the competency development program at BKN. The independent variable is competence, while the dependent variable is employee performance productivity. The results of the analysis show that there is a significant positive relationship between competency development and employee performance productivity. It is known that the coefficient of determination or R² value is 57,1%. This figure means that the competency variable (X1) has an effect on the work productivity variable (Y) by 57.1%. Meanwhile, the remainder (100% - 57.1% = 42.9%) is influenced by other variables outside this equation or variables that were not studied. These findings highlight the importance of investing in competency development as a strategy to increase employee performance productivity at BKN. Managerial implications and policy recommendations are presented to support efforts to develop human resources and increase BKN organizational efficiency. This research provides an important contribution in understanding the dynamics of the relationship between competency and employee performance productivity in the government context.